MENGATASI TANTANGAN DAMPAK KAWASAN INDUSTRI MELALUI PENGUATAN SDM, PEMBERDAYAAN MASYARAKAT, DAN DUKUNGAN UMKM DI DESA NAMBO UDIK, KECAMATAN CIKANDE, KABUPATEN SERANG - Pramudi Harsono; Irwan Sapta Putra; Izzuar Akbar Fawzi; Bagas Ariyanto; Eva Suhayati; Fani Oktarianti Putri Rahayu (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The development of industrial areas has resulted in changes in the social and economic aspects of people in rural areas. Over a significant period, villagers were generally limited to one type of work, resulting in many villages being left behind in development. Increases in rural industrial areas are usually accompanied by further development of roads and other infrastructure. With this increase in facilities, strengthening the capacity of Human Resources through community empowerment and supporting Micro, Small and Medium Enterprises (MSMEs) are three different elements but have the same goal, namely increasing productivity. Based on Law No. 12 of 2012, HR management is an important competency for MSME actors. In addition, to face business challenges in the digital era, MSMEs need to be adaptive and responsive to technological developments. Therefore, this community service program aims to provide an understanding of HR capabilities in the digital era in Nambo Udik Village, Cikande District, Serang Regency. This is done through collaboration with the Bina Bangsa University 2023 KKM group which has a focus on community empowerment and MSMEs. This activity includes presentations, practical training, and mentoring. This method has proven to be very relevant for adoption because the results of this activity show that the target audience has succeeded in recognizing the process of empowering human resources through mentoring assistance